A service-free sensor-based application - Chung, Julian Zhong Wei (Nanyang Technological University, 2023)
This project is called the Smart Indoor Management System (SIMS) and it comprises 3 main components - An entrance Lighting System with Intruder Alarm, Fire Detection System, and Smoke Detection System. All of these are capable of sending notifications to the user’s Telegram through the use of a bot. SIMS is created with the intention to provide automated and smart solutions to improve the quality of living, as well as to improve safety within high-risk premises such as factories and power plants. SIMS is also designed with inclusivity such as providing additional lighting for the visually handicapped. This project uses the Arduino Uno Rev 3 as the main microcontroller, along with the ESP32 CAM module to connect to the Internet for its messaging purpose. Some other hardware includes LEDs, buzzers, resistors, as well as sensor modules like a PIR Motion Sensor, IR Flame Sensor, and an MQ2 Smoke Detector. The microcontroller is fed with code written on the Arduino 1.8.13 IDE using the C/C++ language. Overall, a service-free sensor-based solution is developed with the power source being primarily solar energy, which is harvested from solar panels. Additionally, Maximum Power Point Tracking (MPPT) and Battery Energy Storage Systems (BESS) are implemented with the use of the solar charge controller and a 1.2Ah lead acid battery respectively. Finally, two MATLAB simulations and three experiments are conducted in this project. In the first simulation, it is discovered that MPPT can be implemented with the use of the Perturb & Observe (P&O) algorithm. The second simulation aims to extend beyond the scope of SIMS to integrate the whole system into the grid. The result proves that the Photovoltaic (PV) array can be connected to supply the excess electricity to the Singapore grid at 230Vrms and 50Hz. The first experiment shows that SIMS is capable of powering the Arduino circuit configuration that is set up in this project with an estimated charging time of 10.29 hours. The second experiment highlights the behavior of the lead-acid battery charging under the Constant Current (CC) method. The third experiment focuses on the performance of SIMS with varying solar irradiance and battery capacities.